North american immigrants of Santa Bárbara d’Oeste and Americana and the process of knowledge transmission analogous to that of non-formal technical education (1865-1915) - Soffner, Renato Kraide; Mialhe, Jorge Luís [UNESP] (Universidade Estadual de Maringa, 2023)
This work analyzes the educational role of North Americans emigrated from the United States to Brazil shortly after their defeat in the secession war. The revision of primary and secondary historical sources confirmed the role of immigrants in the offering of non-formal agricultural education to the communities of the region of Americana and Santa Bárbara d’Oeste-SP, in the period 1865 to 1915. Two subjetcs were studied, in search of comprovation of the hypothesis presented, which states that the process of knowledge transmission, analogous to that of non-formal technical education, provided by the North Americans and their immediate descendants would have provoked educational effects on the communities affected.
Inmigrantes nord-americanos de Santa Barbara d’Oeste y Americana y el proceso de transmisión de conocimiento análogo a la educación técnica no formal (1865-1915)
Imigrantes norte-americanos de Santa Bárbara d’Oeste e Americana e o processo de transmissão de saberes análogo à educação técnica não formal (1865 – 1915)
Keywords: confederate emigration; educational process; São Paulo state; technical education